Treatment of Leachate Generated from Sewage Sludge Lagoon - Derum, Aidahapini (2002)
The main objective of this research was to study the treatment of leachate generated from sludge lagoons using anaerobic and aerobic processes. Two methods were used to separate the sludge and leachate in sludge lagoons. The first method used a clay layer at the bottom of the lagoon. While, the second method used a filter media (sand and gravel) and underdrainage. The leachate was generated from four sets of tank with different depths (0.375 m and 0.75 m of sludge). The quality of leachate was measured in tenns of BOD, COD, TSS, VSS, E-coli, ammonia, nitrate, TKN, phosphorus and heavy metal. The results showed that the quality of treated leachate from the sand tanks is better than that of clay tanks. The percentage of BOD, COD, TSS, VSS and E-coli removed for sand tanks ranged from 96-97%, 95-96%, 95-97%, 94-96% and 99-99.5% respectively. While the percentages of BOD, COD, TSS, VSS and E-coli in the clay tanks ranged from between 91-93%, 90-93%, 86-89%, 86-90% and 90-92% respectively. Results show that filtration using sand and gravel is more effective in removing organic pollutant in leachate. Treatment using aeration tanks is effective in removing BOD, COD, TSS, VSS and E-coli. The percentage of removal of BOD, COD, TSS, VSS and E-coli were 95-96%, 96-97% and 99% respectively using 1 day retention time. Kinetic studies were carried out using Monod equations In order to find kinetic constants such as half velocity, Ks, Yield, Y, maximum rate of substrate utilisation, K, microorganism decay, KI and maximum growth rate, !lm. In addition, a prediction model is also studied by using Monod equations.